2001
DOI: 10.1557/jmr.2001.0280
|View full text |Cite
|
Sign up to set email alerts
|

Gradient porosity poly(dicyclopentadiene)

Abstract: This article describes the preparation of gradient porosity thermoset polymers. The technique used is based on polymerizing a solution of cross-linkable dicyclopentadiene and 2-propanol. The forming polymer being insoluble in 2-propanol, phase separation occurs. Subsequent drying of the 2-propanol gives porosities up to 80%. An apparatus was built to produce a gradient in 2-propanol concentration in a flask, resulting in polymerized gradient porosity rods. The resulting materials have been characterized by sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Recently, open porosity, macroporous crosslinked poly(dicyclopentadiene) (PDCPD) has been produced via chemically induced phase separation (CIPS) [1][2][3]. These materials could serve as bases for applications such as membranes, ion-exchange and chromatographic media, solid support resins, carriers, catalysts or adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, open porosity, macroporous crosslinked poly(dicyclopentadiene) (PDCPD) has been produced via chemically induced phase separation (CIPS) [1][2][3]. These materials could serve as bases for applications such as membranes, ion-exchange and chromatographic media, solid support resins, carriers, catalysts or adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the higher porogen concentrations that cause gelation to occur later, thus allowing more time for the stirring to shear the polymerizing droplets. In the same manner, sample M1 not only has the lowest initial porogen concentration, but also is below the critical point, which is defined as the particular composition separating a compositions domain inside of which the porogen precipitates within a polymer matrix (low porogen concentrations) and a domain where polymer particles precipitate within the porogen (high porogen concentrations) 19, 20. In this case, gelation of the microsphere occurs even earlier since it corresponds to the gelation of the PDCPD matrix, while the gelation of the samples with porogen concentrations above the critical point corresponds to the moment where the primary particles (arising from the precipitation of PDCDP within the monomer/porogen mixture) agglomerate.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that chemically induced phase separation (CIPS) can be used to produce monolithic and gradient porosity macroporous thermosets 18–22. This technique consists of polymerizing polymer precursors in presence of an initially miscible, nonreacting porogen.…”
Section: Introductionmentioning
confidence: 99%
“…Such spatially nonuniform processes may play a role in the final physical and mechanical properties of porous polymers, which are formed through precipitation polymerization reactions in the absence of stirring. 43,57,58 This solution method is currently limited by two aspects: The first is a diffusive speed limit, which limits the speed of objects that can be tracked. Currently, this is limited to <10 μm 2 /s based on the mechanical response time of 3D-SMART.…”
Section: ■ Conclusionmentioning
confidence: 99%